ANALISIS KECACATAN PRODUK CRUDE PALM OIL (CPO) MENGGUNAKAN METODE QUALITY CONTROL CIRCLE (QCC) PADA PT.RAMAJAYA PRAMUKTI - St Nova Meirizha; Dian Kristina (Fakultas Teknik UMRI, 2021)
Quality is the overall characteristics and characteristics of a product or service whose ability to satisfy needs, both expressed and implied (Irwan & Haryono, 2015). In this era of increasingly competitive industrialization, every business person who wants to win the competition in the industrial world will pay full attention to quality. QCC is a new concept to improve the quality and productivity of industrial/service work. It is evident that one of the success factors of industrialization in Japan is the effective implementation of QCC. In this research journal, the quality of crude palm oil (CPO) levels is decreasing. There are 3 types of defects, namely levels of FFA (Free Fatty Acids), levels of Moisture (Water) and levels of Dirt (Stool). Of these three, the most dominant are FFA levels and Moisture levels. Free fatty acid content (FFA) of 158 samples tested contained 150 samples of free fatty acids (FFA) which were outside the company standard. Then followed by moisture content with a total defect of 45 samples from 158 test samples. At the level of dirt (Dirt) there are absolutely no samples that are outside the company's standards.